Managing functional neurological disorder: treatment recommendations for health professionals in Australia - Alexander Lehn; Megan Broughton; Vince Cheah; Tjerk J Lagrand; Jessica Davis; David Palmer; Dharsha Petrie; Cindy Bradbury; Rianna Guest; Alana Schuurs; Jacinta Lewis; Rebecca Madden; et al. (BMJ Neurology Open)
Functional Neurological Disorder (FND) can present significant management challenges due to its sometimes-complex presentation and the historical stigma attached to this diagnosis. Recent advances have improved understanding and management of FND, emphasising the benefit of a multidisciplinary approach to management. The prognosis of FND varies but evidence-based treatments offer the potential of remission to many people for whom FND might otherwise cause long-term disability, and meaningful symptomatic and functional improvement for many more. Despite this, limited and inequitable access to treatment means that many people with FND in Australia continue to experience treatable disability due to the condition.Diagnosis: FND should be diagnosed based on positive signs rather than exclusion. This includes identifying inconsistencies and incongruencies in symptoms that differentiate them from other neurological conditions.Communication: The diagnosis of FND should be communicated to patients promptly and clearly upon diagnosis of the condition. Information provided should include the name of the condition, the basis on which the diagnosis has been made, key principles that can aid self-management, and shared planning of next steps in treatment or accessing treatment.Multidisciplinary Management: Across healthcare service models, treatment should involve a multidisciplinary team to address the multifaceted, and sometimes complex symptoms of FND.Role of General Practitioners (GPs): GPs are integral in the long-term management of FND, providing continuity of care, patient support and education, and facilitating access to specialist services. An informed GP can provide the patient with confidence and agency to be pro-active in their symptoms.Main RecommendationsDiagnosis: FND should be diagnosed based on positive signs rather than exclusion. This includes identifying inconsistencies and incongruencies in symptoms that differentiate them from other neurological conditions.Communication: The diagnosis of FND should be communicated to patients promptly and clearly upon diagnosis of the condition. Information provided should include the name of the condition, the basis on which the diagnosis has been made, key principles that can aid self-management, and shared planning of next steps in treatment or accessing treatment.Multidisciplinary Management: Across healthcare service models, treatment should involve a multidisciplinary team to address the multifaceted, and sometimes complex symptoms of FND.Role of General Practitioners (GPs): GPs are integral in the long-term management of FND, providing continuity of care, patient support and education, and facilitating access to specialist services. An informed GP can provide the patient with confidence and agency to be pro-active in their symptoms.Changes in Management as a result of the recommendationsThe recommendations advocate for a shift from a pure psychiatric framework to a multidisciplinary and person-centred approach. Employing the biopsychosocial framework can enhance patient outcomes, including addressing protective and risk factors for Aboriginal and Torres Strait Islander people.